Efektivitas Media Pembelajaran Interaktif Dalam Meningkatkan Minat Belajar Pendidikan Jasmani Dalam Permainan Bola Voli - ., Nurul Aulia Silvianti; ., Novri Gazali (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The purpose of this study is to find out how the effectiveness of interactive learning media in increasing interest in learning physical education in volleyball games. The typeof this research is an experiment, the population and sample in this study are students of class XI IPS 2 SMA N 3 Siak Hulu, which consists of 30 students. The research instrument was used through 3 stages, namely the Pree Test (initial test of giving an interest in learning questionnaire) then giving treatment (interactive learning touch) and finally the Post Test (giving a questionnaire of interest in learning again). Based on the results of the research data analysis, it can be concluded that there is an influence from the interactive method in increasing interest in learning physical education in volleyball games. This is shown from the amount of t-count from t-table (3.055 > 2.052) or 11%.